O New York Times na cobertura das eleições brasileiras de 2010: foco em Dilma Rousseff - Dota, Maria Inez Mateus (Estudos Linguísticos (São Paulo. 1978), 2016)
This paper aims at verifying which discursive strategies and news structures are employed by The New York Times to present the candidate Dilma Rousseff to its readers, during the 2010 presidential campaign. It is based on the theoretical and methodological foundations of Discourse Analysis and Journalism Studies that offer subsidies for subjects such as intertextuality, interdiscursivity, modality, irony, as well as for the framings used by the newspaper and the consequent sub-themes explored.